The Effect of Personal Selling and Skills on Consumer Interest in Nuriza Mart in Meureudu District, Pidie Jaya Regency - Teuku Isnaini; Cut Yusnidar; Nadia Nadia (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to determine "The Influence of Personal Selling and Skills on Consumer Interest in Nuriza Mart in Meureudu District, Pidie Jaya Regency". Where the independent variables are Personal selling (X1) and Skills (X2) and consumer interest (Y) as the dependent variable. The population in this study are consumers who buy consumers at Nuriza Mart in Meureudu District, Pidie Jaya Regency, where there are 100 consumers. The entire population in this study was taken as a sample. Data were collected using a survey method through questionnaires filled out by respondents. Then the data obtained were analyzed using multiple regression analysis. This analysis includes Validity Test, Reliability Test, Multiple Regression Analysis Classical Assumption Test, Hypothesis Testing through F Test and t Test, and Analysis of the Coefficient of Determination (R²). Based on the results of the study, the regression equation was obtained: Y = 3.838 + 0.422 X1 + 0.426 X2. Based on the results of the analysis above, it can be concluded that from the two variables studied, it turns out that the Skills variable (X2) has the most dominant influence of 42.6% on consumer interest in Nuriza Mart in Meureudu District, Pidie Jaya Regency. The relationship between the dependent and independent variables, namely Personal selling (X1) and Skills (X2) variables on consumer interest at Nuriza Mart in Meureudu District, Pidie Jaya Regency with a correlation index of 81.1% This means that the relationship is very strong. Then the index of determination of each variable Development of Personal selling (X1) and Skills (X2) variables is 67.5%, this means that it has a significant effect on consumer interest in Nuriza Mart in Meureudu District, Pidie Jaya Regency and by 32.5% which is influenced by other variables not examined in this study.